Studi Eksperimen Pengujian Kuat Tekan Beton Pasca Bakar terhadap Beton Normal - Andi Sulfanita; Imam Fadly; Muh. Syahril; Andi Sitti Nurfadilah Ruslan (Universitas Batanghari Jambi, 2023)
The increasing number of building fires in Indonesia every year especially in big cities is the reference for this research. Where this can affect every construction including the existing concrete structure in the building. The purpose of this study will be to discuss color changes, physical and strength as well as the percentage decrease in concrete compressive strength due to high temperatures after 1, 2, and 4 hours of combustion. Using an experimental method of post-combustion concrete compressive strength and tested when the concrete age reaches 28 days which was carried out in September-December 2021. The results of this study showed that the quality of the concrete was 25 MPa with a combustion duration of 1, 2, and 4 hours, respectively. – reached temperatures of 190°C, 300°C, and 410°C, respectively, resulting in average compressive strength of 21.7 MPa, 18.3 MPa, and 13.2 MPa, causing a percentage decrease in compressive strength of up to 19.3%, 31,9%, and 50.9%. The color changed which was initially grayish white to yellowish white then brownish gray to blackish, and the normal surface experienced fine, rough cracks to peeling at the corners.